RISK FACTORS FOR RELAPSE AMONG YOUNG AFRICAN ADULTS FOLLOWING IN-PATIENT TREATMENT FOR DRUG ABUSE IN THE GAUTENG PROVINCE - Crafford, Gretel (Social work, 2016)
More than 20% of admissions into treatment centres are re-admissions, with high incidences among young African adults in the Gauteng Province. Drug abuse and relapse have a negative impact on the achievement of social development goals in South Africa, and make serious demands on social work services. This study determined the risk factors for relapse among young African adults following in-patient treatment for drug abuse, specifically according to gender in order to propose localised and gender-specific treatment programmes and aftercare/reintegration services. A survey was undertaken with 44 respondents, who completed a group-administered questionnaire, at treatment centres across the Gauteng Province